1998
DOI: 10.1029/97ja02632
|View full text |Cite
|
Sign up to set email alerts
|

Multipoint study of a substorm on February 9, 1995

Abstract: Abstract. An extended interval of strong northward interplanetary magnetic field (IMF) was observed by the Wind spacecraft located at an upstream distance of-193 Roe from February 8-10, 1995, with a brief break of southward IMF from 0200 to 0400 UT on February 9. This brief interval of southward IMF led to an isolated substorm of moderate intensity (-500 nT) with expansion phase starting at -0431 UT. This substorm may be triggered by the northward turning of the IMF since its onset time matched well with the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2000
2000
2009
2009

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Alternative models have suggested diverse mechanisms for the principal cause of substorms including current disruption (CD) with a "cross-tail current partial disruption" [Rothwell et al, 1988;Lui, 1996;Lui et al 1998;Kan, 1998 is not excluded as the result of the CD. The two approaches (CD and NENL) also differ in the physics of the local plasma instabilities that are responsible for the active phase onset.…”
Section: Introductionmentioning
confidence: 99%
“…Alternative models have suggested diverse mechanisms for the principal cause of substorms including current disruption (CD) with a "cross-tail current partial disruption" [Rothwell et al, 1988;Lui, 1996;Lui et al 1998;Kan, 1998 is not excluded as the result of the CD. The two approaches (CD and NENL) also differ in the physics of the local plasma instabilities that are responsible for the active phase onset.…”
Section: Introductionmentioning
confidence: 99%
“…This substorm has been extensively studied [Lui et al, 1998]. Owing to an unusually long northward interplanetary magnetic field, the magnetosphere was as close to a low energy or "quiet" state as is likely possible ß before a substorm.…”
Section: February 9 1995mentioning
confidence: 99%
“…A further connection with a localized increase in the nightside reconnection rate was also found. Lui et al (1998) observed a possible relation between BBFs and optical auroral signatures moving equatorward, while Lyons et al (1999) found that BBFs were more frequent and stronger during periods of PBIs, compared to periods without PBIs. Although a oneto-one correlation between PBIs and BBFs could not be confirmed, Zesta et al (2006) could associate all of their observed PBIs with fast flow channels in the tail, occurring in the same local time sector.…”
Section: T Johansson Et Al: Electric Field Associated With a Bbf-limentioning
confidence: 99%